EFEKTIVITAS KOMUNIKASI PEMASARAN DIGITAL TERHADAP KESADARAN MEREK DAN KEPUTUSAN PEMBELIAN APARTEMEN MAJESTIC POINT SERPONG SELAMA PANDEMI COVID-19 - Rahmawati, Sri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This study aims to determine the effectiveness of digital marketing communications on brand awareness and purchasing decisions at Majestic Point Serpong Apartments during the Covid-19 pandemic by using quantitative approach techniques and data sources obtained by distributing questionnaires to prospective buyers of Majestic Point Serpong Apartment units as many as 80 respondents. Then, the method used is simple regression analysis. The results of this study indicate the Effectiveness of Digital Marketing Communications (X) has a significant positive effect on Brand Awareness (Y1) with a t count of 5.410. Digital Marketing Communication Effectiveness Variable (X) has a significant positive effect on Purchase Decision (Y2) with a t value of 7.214. Brand Awareness Variable (Y1) on Purchase Decision (Y2) has a positive effect with a value of 0.494. And the variable Purchase Decision as a full intervening variable